Coleoptera of Genting Highland, Malaysia: species richness and diversity changes along the elevations - Musthafa, Muneeb M.; Abdullah, Fauziah (Museu de Ciències Naturals de Barcelona, 2019)
The objective of this study was to measure beetle richness and diversity in Genting Highland at four major elevations (500 m, 1,000 m, 1,500 m and 1,800 m). Beetles were collected using light traps, malaise traps and pitfall traps. Altogether, 1,499 beetle samples representing 156 morphospecies were collected. Light trap and pitfall traps were more effective than Malaise trap. The 500 m elevation band displayed high species richness, abundance and diversity with all indices showing a decreasing pattern. The species accumulation curve displayed a progressive asymptote for all the altitudinal transects, showing the sampling effort was sufficient for this study. A long–term monitoring program of beetle diversity and distribution is useful to test abiotic factors that might influence biodiversity. This study also serves as a benchmark for further studies on this highly disturbed montane cloud forest in Peninsular Malaysia and will be useful to implement effective conservation management, particularly under the threat of climate change. © 2019 belongs to the authors.